Meaning making in early childhood research pedagogies and the personal - Parnell, Will 1968- (Changing images of early childhood, 2018)
Meaning Making in Early Childhood Research asks readers to rethink research in early childhood education through qualitative research practices reflective of arts-based pedagogies. This collection explores how educators and researchers can move toward practices of meaning making in early childhood education. The text’s narrative style provides an intimate portrait of engaging in research that challenges assumptions and thinking in a variety of international contexts, and each chapter offers a way to engage in meaning making based on the experiences of young children, their families, and educators.--Provided by publisher.